Pelaksanaan Perjanjian Perseroan Terbatas Pertamina dengan Pengusaha Stasiun Pengisian Bahan Bakar Umum No.24.361.83 dalam Penyediaan Bahan Bakar Minyak - Nazifah, Nazifah; Somad, Kemas Abdul; Cahyani, Vitalia (Universitas Batanghari Jambi, 2025)
Article 33 paragraph (3) of the 1945 Constitution states that the earth, water, and natural resources contained therein are controlled by the state and used as much as possible for the prosperity of the people. Oil and natural gas are strategic and non-renewable natural resources. As natural resources contained in the Indonesian mining jurisdiction, the implementation of oil and natural gas business activities in Indonesia is fully carried out by the state. To realize the objectives of developing the oil and natural gas business, the government delegates authority to PT. Pertamina (Persero) as a State-Owned Enterprise (BUMN) to carry out activities that include the management of oil and natural gas mining, as well as its distribution to all corners of the country. The agreement between PT. Pertamina and the entrepreneur of SPBU No. 24.361.83 Broni regarding the management and distribution of fuel oil is made in writing and stated in a deed in the form of a Letter of Agreement for the Appointment and Management of Public Fuel Filling Stations (SPPPS) regarding the distribution of fuel oil. In reality, several things have emerged that have become problems experienced by SPBU No. 24.361.83 Broni, namely the problem in the distribution of fuel oil that is late for distribution. Another problem that arises is the loss due to the difference in the volume of fuel oil measurements so that the amount of fuel oil distributed by the Pertamina Depot to SPBU No. 24.361.83 Broni is different from the amount previously ordered and paid by the SPBU. The purpose of this study is to determine and analyze the implementation of the agreement, Pertamina Limited Liability Company (Persero) with the public fuel filling station No. 24.361.83 Broni Jambi in the provision of fuel oil, the obstacles faced and efforts to overcome the obstacles. The research method used in this study is the empirical juridical research type. The approach used in this study is socio-legal research. The results of the study indicate that the implementation of the cooperation agreement between the public fuel filling station (SPBU) No. 24.361.83 in Broni with PT. Pertamina has not been implemented properly. The obstacles faced during the agreement period between PT Pertamina (Persero) and SPBU No. 24.361.83 Broni, namely the delay in filling fuel oil at the Pertamina depot, the lack of oil received as ordered 5000 liters but only 3980 liters received.